Correlation between prenatal and postnatal ultrasound diagnosis of fetal hydronephrosis - Vilà Famada, Anna (2019)
about 20-30% of them are urogenital and among them 50% are fetal urinary tract dilatations (UTD). Objective: To establish the correlation between prenatal and postnatal hydronephrosis diagnosis, as well as to analyze the prognosis. Design, patients, interventions and main outcome measure: Retrospective observational study performed by the Prenatal Diagnosis Unit of Parc Taulí Hospital (Sabadell), which included 177 pregnant women with ultrasound diagnosis of UTD between January 2011 and December 2016. We performed a descriptive analysis of the most important ultrasound and perinatal variables. The main outcome measure was the degree of dilatation of UTD. Results: The prevalence of HNF was 1.17%; 82.8% were diagnosed in the second trimester ultrasound; 42.9% of fetal hydronephrosis cases were bilateral and, in 95.6%, the urogenital pathology was not associated with other malformations. Congenital heart disease was the most frequently associated prenatal anomaly (3.3%). Among 93 low-risk hydronephrosis cases diagnosed in the second trimester, 53.8% resolved spontaneously in the third trimester, 30.1% remained stable and 16.1% worsened. Of the 32 cases of moderate-severe UTD diagnosed in the second trimester, only 9.4% improved in the third trimester. Complementary examination was required in 46.9% of the neonates and 14.1% required surgical intervention. Conclusions: Most cases of fetal hydronephrosis were diagnosed by second trimester ultrasound. Mild UTD presents good prognosis as opposed to moderate-severe cases, which usually persist after birth.